Occupational Stress and Employee Performance - Pant, Dinesh Kumar (The Management Review, 2025)
Employee performance is a crucial factor in achieving organizational success, as it significantly impacts productivity, profitability, and overall business outcomes. This study investigates the impact of occupational stress on employee performance at Nepal Telecom Ltd., focusing on four major predictors: working environment, workload, salary and benefits, and job security. The research aims to understand how occupational stress influences employee efficiency and organizational effectiveness in the telecommunications sector. Data were collected from 325 employees using a structured questionnaire and convenience sampling. The study used Pearson's correlation and regression analysis to evaluate the correlation between predictors and employee performance, revealing that working environment, workload, salary and benefits, and job security significantly positively impact employee performance at Nepal Telecom Ltd. A supportive work environment, balanced workload, competitive salary and benefits, and job security collectively enhance employee performance by fostering comfort, motivation, and focus while minimizing stress and anxiety. The study highlights the importance of managing occupational stress and recommends creating supportive work environments, balancing workloads, offering competitive compensation, and ensuring job security to optimize employee performance.